Long-term herbivore population dynamics in the northeastern Qinghai-Tibetan Plateau and its implications for early human impacts - Huang, Xiaozhong; Zhang, Jun; Storozum, Michael; Liu, Sisi; Gill, Jacquelyn L.; Xiang, Lixiong; Ren, Xiuxiu; Wang, Jiale; Qiang, Mingrui; Chen, Fahu; Grimm, Eric C. (Review of palaeobotany and palynology, 2020)
Large herbivores are keystone species on the Qinghai-Tibet Plateau (QTP), but their past population ecology is the product of a complex combination of climatic changes and human activities that span the Holocene. In this study we use the record of dung-residing fungal spores (Sporormiella) in the stratified lake sediments of Genggahai Lake in the northeastern QTP to track changes in large herbivore populations. We hypothesize that the abundance of Sporormiella spores would decrease with the reduction of herbivore populations with the retreat of the summer monsoon after the mid-Holocene and the resulting vegetation degradation which is indicated by the pollen record. However, our results reveal an increase in Sporormiella spores after 5.7 ka (1 ka = 1000 cal yr BP), suggesting an increase in herbivore populations. Combined with regional archeological evidence, we infer that hunter–gatherers may have influenced the regional herbivore ecology and that the early Tibetan people may have domesticated or managed yaks and other herbivores in the northeastern QTP since 5.7 ka. The records of Sporormiella spores are interpreted within a robust chronostratigraphic framework provided by numerous radiocarbon dates from regional archeological sites, and the representation of Sporormiella spores during the Tang Dynasty is tested by a comparison with historical records of the livestock population of the region. Our findings potentially improve understanding of early human adaptation to environmental changes and past herbivore-steppe ecology in the QTP during the Holocene. •The first well-dated Last Deglacial dung-related fungal spores record in China.•Discussed the earliest human impact on animal ecology on the highest plateau.•Proposed the earliest herbivore management on the key area of QTP.